‘I Feel Disempowered Because I Could Not Do Anything’: Clinical Facilitators' Perception of Violence Towards Nursing Students During Clinical Placement - Hila Ariela Dafny; Paul Cooper; Nasreena Waheed; Stephanie Champion; Christine Mccloud; Nicole Snaith; Leeanne Pront (Nursing Open)
ABSTRACT Aims To explore clinical facilitators' understanding, experiences and perceptions of their role in supporting registered nurse students (RNS) who experience workplace violence (WPV) during clinical placement. Design An exploratory, qualitative design. Methods and Data Source Data were collected between September and November 2022 using semi‐structured interviews of 1‐h duration with 11 clinical facilitators working in South Australia. The interviews were transcribed verbatim and analysed using thematic analysis. Results Participants reported that WPV is experienced in many forms, including verbal and physical violence towards RNS during clinical placements. Clinical facilitators are not always aware of this experience and have mixed abilities to resolve the damage. Most importantly, clinical facilitators saw themselves as disempowered to provide the support required by RNS after WPV incidents as they perceived themselves as visitors to the facilities. Conclusion Findings indicate that a clinical facilitator's scope and ability to support a RNS is often not at a level where real impact and safety can occur. Varying perceptions of what WPV is, what is acceptable, and the authority or influence of a clinical facilitator have all informed this issue and need to be considered in developing strategies to address WPV towards RNS. Implications for the Nursing Profession This study highlights that by understanding the causation of WPV and recognising the lack of influence and scope of clinical facilitators to act to support RNS during WPV events, positive industry changes can be instigated to promote student placement experiences and healthcare provision. Impact Clinical facilitators felt limited in their role to support RNS experiencing WPV. This research impacts future nursing students, education providers, clinical facilitators and clinical placement providers. Reporting Method COREQ guidelines were utilised to report qualitative research. No Patient or Public Contribution This paper explores specifically the clinical facilitators' perceptions of WPV.